132 Evaluation of the normal pressure hydrocephalus (NPH) service at Wessex Neurological Centre. Issue 6 (27th May 2022) - Hopkins, Molly; Jones, Charis; Anwar, Durria-Rubat; Kipps, Christopher; Pengas, George
Abstract : Background: NPH is a condition in which ventriculomegaly occurs due to accumulation of cerebrospinal fluid (CSF). The hallmark symptoms are a triad of abnormal gait, cognitive impairment and urinary inconti- nence. A lumbar puncture (LP) is the main diagnostic test and treatment is via a ventriculoperitoneal shunt. Aim: To evaluate the current service delivered and to identify factors that may improve the identification of patients most likely to benefit from treatment. Method: This is a retrospective study including 126 patients referred between January 2015 and September 2017. From clinical notes, variables were recorded including demographics, imaging, presence of dispro- portionally enlarged subarachnoid spaces (DESH), LP results, CSF Alzheimer's disease (AD) biomarkers, surgery outcome and complications. Results: The shunt success rate was 78.6% and the complication rate was 9.5%. The positive predictive value of an LP and DESH in predicting good shunt outcome was 82.5% and 77.3% respectively. There was no statistical significance between variables assessed and a positive or negative NPH diagnosis. Conclusion: Our service had higher surgical success rates and lower complication rates than stated in literature. The most diagnostically accurate test is a LP, this should be done regardless of DESH. Demo- graphics and CSF biomarker analysis were not diagnostically helpful. mrkh1g17@soton.ac.uk